Bibliometric Methods: Analysis of the Development Potential of Ethnoscience-based Science Literacy Modules in Chemistry Learning - Rahmawan, Setia; Rahayu, Dea Santika (Indonesian Journal of Science and Education, 2023)
There still needs to be more research on the potential analysis of the development of ethnoscience-based science literacy modules in chemistry learning using bibliometric tools. Ethnoscience-based science literacy modules still need to be found and used in chemistry learning. This research aims to analyze the novelty and effectiveness of ethnoscience-based science literacy modules in chemistry learning. The subject of this research is a science literacy module based on ethnoscience in chemistry learning. In this study, the researchers also analyzed articles that have been filtered based on topics based on local wisdom-based science literacy modules. The analysis contains several components: title, year, doi, author, method, outcome, and conclusion. The research uses an approach that uses the method of Systematic Literature Network Analysis (SLNA) assisted by bibliometric tools as the medium used in analyzing the article. The data obtained was many articles from the SCOPUS database, which had previously defined some criteria for capturing it. The criteria are related to the year of publication, keyword, and language selection. The application used in this study is the VOS Viewers application. The results show that research related to ethnoscience-based science literacy modules in chemistry learning is still highly feasible, given the numerous constraints in some schools. However, it should be noted that ethnoscience-based science literacy cannot replace scientific literacy globally because of the global literacy capabilities needed in everyday life.